DU/DI RELEVANCE THROUGH IMPROVING COMMUNICATION SKILLS FOR SMK STUDENTS (CASE STUDY IN MANDARIN) - Silvia Rahmi; R. Madhakomala (Interdisciplinary Journal of Advanced Research and Innovation, 2024)
Mandarin proficiency is an essential 21st-century skill. However, current instructional materials and partnerships with DUDI must be improved to develop students' practical communication abilities. This article analyzes the Business and Industrial World (DUDI) relevance by improving Mandarin communication skills for vocational high school students to enhance their employability. Literature reviews of data from the Central Statistics Agency and analysis of government regulations were conducted to formulate a conceptual framework. The framework underlines the need for a competency-based curriculum, contextual teaching materials, and collaborative training programs between schools and companies in the field of Mandarin language. Students' listening and speaking abilities need particular improvement to meet professional communication demands. On the other hand, collaboration between SMK and DUDI has been minimal, mostly limited to internship programs without substantive cooperation in curriculum or materials development. DUDI plays a vital role in formulating competency standards tailored to industry needs. The materials should be competency-based and interactive and encourage active communication skills. Trials of such tailor-made curricula have confirmed improved language performance in class. This model needs to be expanded to more SMK nationwide. Thus, increased synergy in customizing Mandarin training to DUDI requirements promises to bolster the competitiveness and absorption of graduates. This will ultimately support national economic productivity through better-skilled human resources.